The anthelmintic effect of copper oxide wire particle (COWP) boluses against Haemonchus contortus in indigenous goats in South Africa - Vatta, Adriano Francis (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2009.